Psychometric Analysis of the Experiences in Close Relationships Questionnaire (ECR-12) in the Adult LGBT+ Population of Peru - Alegre Bravo, Alberto Agustín (2025)
The Experiences in Close Relationships Questionnaire (ECR, Brennan et al., Attachment Theory and Close Relationships, 1998) is one of the most widely used measures of adult romantic attachment. Despite the advantages of the ECR, its length may discourage its use in clinical and research contexts. Consequently, the aim of this study was to conduct a psychometric analysis of the instrument validated by Guzmán-González et al. (2020), which constitutes a brief Spanish version of the ECR, and to examine its psychometric properties in the Peruvian LGBT+ population. A total of 551 participants from the LGBT+ community participated in the study. A confirmatory factor analysis revealed an initial two-factor structure (anxiety and avoidance) with the 12 proposed items, but the fit indices were unsatisfactory. Upon analyzing the standardized factor loadings, it was evident that item 11 (a reverse-scored item) needed to be removed, which improved the fit indices (RMSEA = 0.074, CFI = 0.950, TLI = 0.935). Reliability coefficients for anxiety and avoidance were .897 and .904, respectively. The findings are discussed.